Prototype of Population Census Data Processing Information System at Beo Village Office, Talaud Archipelago Regency Based on Website - Debi Uada; Eliyah A M Sampetoding; Hoxy R Taluay; Monica Natalin; Esther Sanda Manapa (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Beo sub district office has not utilized the information system in processing population census data. Data recording and population census information services are still done manually so that village office employees often experience problems in meeting requests for data and information on population censuses. In addition, decisions and policies by the village heads regarding the population census are often not effective, well targeted, and timely because population census information is often irrelevant. Responding to this phenomenon , it is deemed necessary to create an information system for processing population census data. In this study was built by adapting the concept of qualitative research and modified SDLC method. The SDLC method is part of a software development method with the initial stage of software requirements analysis and the final stage being design. The result of the study indicate that the information system must provide three finctions, namelly users, employees, and village heads.